Thermal Performance of Banana Peel Biocomposites for Tropical Building Insulation - Deni Priansyah; Benedicta Putri Pelealu; Dimas Handriyanto; Alya Putri Yulianti (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2026)
The construction industry is a major contributor to global carbon emissions, largely due to the use of conventional materials with high thermal conductivity. This highlights the need for environmentally sustainable insulation materials aligned with circular economy principles. As the world’s fourth-largest banana producer, Indonesia generates vast amounts of banana peel waste that can be repurposed as an eco-friendly thermal insulation material.This study evaluates the thermal performance of banana peel-based biocomposite (BP80-PS20) as an insulation material for tropical buildings. The research employed a systematic literature review and numerical simulations using DesignBuilder software on a simplified model of a tropical house. Key parameters analyzed include thermal conductivity, U-value, and R-value, benchmarked against Indonesian (SNI 6389:2011) and international (ASHRAE 90.1-2019) standards. Simulation results indicate that BP80–PS20 significantly improves thermal resistance, reducing wall U-values from 2.97 to 0.68 W/m²K and partition U-values from 1.64 to 0.30 W/m²K, corresponding to an increase of over 300% in R-value. The insulated building maintained indoor temperatures between 24.5°C and 27.2°C, which fully falls within the SNI and ASHRAE comfort zones. These findings confirm that banana peel waste can serve as a sustainable thermal insulation material, enhancing building energy efficiency and promoting green construction practices in tropical climates.